2017
DOI: 10.1093/neuonc/nox152
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells as natural biofactories for exosomes carrying miR-124a in the treatment of gliomas

Abstract: MSCs can be used as natural biofactories to produce Exo-miR124, which is an effective antiglioma agent worthy of further clinical evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
135
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(149 citation statements)
references
References 36 publications
(48 reference statements)
4
135
0
Order By: Relevance
“…From then on, MEVs have been increasingly considered as substitutes for MSCs in drug delivery. Efforts have been made to improve the efficacy of MEV-based drug delivery for clinical use (Cheng et al, 2018b;Lang et al, 2018;Sharif et al, 2018;Jo et al, 2019;Li et al, 2019a;Perets et al, 2019;Riazifar et al, 2019). For example, a good manufacturing practice (GMP) standard for large-scale clinical MEVs production based on bioreactor has been established (Mendt et al, 2018).…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…From then on, MEVs have been increasingly considered as substitutes for MSCs in drug delivery. Efforts have been made to improve the efficacy of MEV-based drug delivery for clinical use (Cheng et al, 2018b;Lang et al, 2018;Sharif et al, 2018;Jo et al, 2019;Li et al, 2019a;Perets et al, 2019;Riazifar et al, 2019). For example, a good manufacturing practice (GMP) standard for large-scale clinical MEVs production based on bioreactor has been established (Mendt et al, 2018).…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Exosomes can be enriched from peripheral blood samples and can be used to detect various proteins, lipids, and nucleic acids [17]. Exosomes have been used as drug delivery vehicles for the treatment of several CNS diseases [11,[18][19][20][21]. Exosomes are currently under investigation as therapeutic options for stroke [22].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests the idea of taking exosomes for drug delivery. Several studies have reported that exosomes can be engineered as delivery vehicles by transferring functional biomolecules to cancer cells . Kamerkar et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that sFlt‐1 possesses anti‐tumor effects by inhibiting angiogenesis in many cancers . In addition, several studies have found that exosomes can be engineered as delivery vehicles for transferring functional biomolecules such as proteins, lipids, and nucleic acids (DNA, mRNA, and miRNA) to target cells …”
Section: Introductionmentioning
confidence: 99%